2017
DOI: 10.1080/19420862.2017.1366395
|View full text |Cite
|
Sign up to set email alerts
|

Identification of multiple serine to asparagine sequence variation sites in an intended copy product of LUCENTIS® by mass spectrometry

Abstract: Patent expiration of first-generation biologics and the high cost of innovative biologics are 2 drivers for the development of biosimilar products. There are, however, technical challenges to the production of exact copies of such large molecules. In this study, we performed a head-to-head comparison between the originator anti-VEGF-A Fab product LUCENTIS® (ranibizumab) and an intended copy product using an integrated analytical approach. While no differences could be observed using size-exclusion chromatograp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 41 publications
1
16
0
Order By: Relevance
“…They checked the results with a MS detection and exposed a difference of 27.01 Da (6-9 %). The analysis of MS/MS spectra confirmed serine to asparagine substitution on the light chains [33]. The same year, disulfide isomers were separated with a high resolution.…”
Section: Technical Considerationsmentioning
confidence: 78%
See 1 more Smart Citation
“…They checked the results with a MS detection and exposed a difference of 27.01 Da (6-9 %). The analysis of MS/MS spectra confirmed serine to asparagine substitution on the light chains [33]. The same year, disulfide isomers were separated with a high resolution.…”
Section: Technical Considerationsmentioning
confidence: 78%
“…Inter and intra-vial homogeneity was evaluated, and excellent standard deviation were calculated (0.053 for intra-vial and 0.0137 for inter-vial). Griaud et al and Miao et al reported two comprehensive studies using an array of orthogonal techniques and strategies including CE-SDS for biosimilarity assessment [33,34]. They compared the electropherograms of intact and reduced mAbs and their biosimilar candidate.…”
Section: Size Variants Assessmentsmentioning
confidence: 99%
“…As discussed in Section 5, the significant difference of hydrophobicity between the two parent mAbs (HIC retention times of around 15 min vs. 45 min observed by running a generic linear inverse salt gradient) was likely to explain the unexpected SEC behavior [49]. Last but not least, biosimilarity evaluation also often includes SEC comparability studies for mAb [50,51], ADC [52], granulocyte colony stimulating factor (G-CSF) [53] and erythropoietin (EPO) [54] products.…”
Section: Application Of Modern Uhp-sec To Real Case Studymentioning
confidence: 99%
“…The heterogeneities in the mAb product further complicate its purification. Although a therapeutic protein is often considered a single entity for simplicity, it is a distribution with variations in amino acid sequence (Li et al, 2016; Parker, Pollard, Friesen, & Stanners, 1978; Santos & Tuite, 1993; Tan et al, 2012), higher‐order structure and posttranslational modifications (PTMs; Griaud et al, 2017). PTMs include glycosylation, phosphorylation, C‐terminal lysine truncation, and chemical modifications such as oxidation, deamidation, and isomerization.…”
Section: Introductionmentioning
confidence: 99%